ADOLESCENTS' SENSE OF COHERENCE VS COPING IN STRESSFUL SITUATIONS. PILOT STUDY - Konaszewski, Karol; Danilewicz, Wioleta; Sosnowski, Tomasz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The objective of the article is the answer to the question if the level of the sense of coherence is linked with stress-coping styles in the group of subjects. It was assumed that in the group of youth the sense of coherence would positively correlate with stress-coping strategies based on problem-solving and looking for social contacts, whereas negatively with strategies based on emotion display (Płaczkiewicz, Tucholska 2009).The study was conducted on a group of 149 teenagers of both sexes, aged 14-18 years. The research employed the Life Orientation Questionnaire (SOC-29) by A. Antonovsky and the Coping Inventory for Stressful Situations (CISS) Questionnaire by N.S. Endler and J.D.A Parker. In the group of youth, correlation coefficients indicate a moderate, positive relationship of the sense of coherence and a sense of comprehensibility with a task-focused style. There was also a positive correlation between the general sense of coherence (and three components: a sense of comprehensibility, a sense of manageability and a sense of meaningfulness) and looking for social contacts. Statistically significant correlation coefficients were also obtained between the emotion-focused style and the general sense of coherence and its two components. The  results of this study have important implications. They allow for a better understanding of the sense of coherence that contribute to the stress-coping styles among youth. Future interventions could be based on the strengthening of sense of coherence in analyzed group.